2019
DOI: 10.3390/molecules24071311
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Triazole-Containing Pyrazole Ester Derivatives as Potential Antibacterial Agents

Abstract: To develop new antibacterial agents, a series of novel triazole-containing pyrazole ester derivatives were designed and synthesized and their biological activities were evaluated as potential topoisomerase II inhibitors. Compound 4d exhibited the most potent antibacterial activity with Minimum inhibitory concentration (MIC) alues of 4 µg/mL, 2 µg/mL, 4 µg/mL, and 0.5 µg/mL against Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, and Salmonella gallinarum, respectively. The in vivo enzyme inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Pyrazole is an important five‐membered heterocycle, which can be found in many drugs or pesticides . In the recent years, lots of succinate dehydrogenase inhibitors contain pyrazole motif , such as penthiopyrad, sedaxane, pydiflumetofen, bixafen, isopyrazam, and pyrapropoyne fluxapyroxad.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole is an important five‐membered heterocycle, which can be found in many drugs or pesticides . In the recent years, lots of succinate dehydrogenase inhibitors contain pyrazole motif , such as penthiopyrad, sedaxane, pydiflumetofen, bixafen, isopyrazam, and pyrapropoyne fluxapyroxad.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus DNA gyrase and 5× reaction buffer [40 mM Hepes KOH (pH 7.6), 500 mM potassium glutamate, 2 mM ATP, 0.05 mg/ml albumin, and 10 mM DTT] were obtained from Enzo Biochem (New York, America). The efficacy of DNA gyrase to supercoil relaxed DNA in the presence of ciprofloxacin (CIP, positive control) and IDAR was determined by gel electrophoresis [ 30 , 31 ].…”
Section: Enzyme Inhibition Assaymentioning
confidence: 99%
“…Several recent studies demonstrated drug resistance for their recommended antibiotic therapy with increasing prevalence in parasitic protozoa including Trypanosoma, Plasmodium, Toxoplasma gondii, Leishmania, and Entamoeba. [13][14][15][16] During the early stages of medicinal chemistry development, scientists were primarily concerned with the isolation of medicinal agents found in plants. Today, scientists in this field are also equally concerned with the creation of new synthetic drug compounds.…”
Section: Original Articlementioning
confidence: 99%